Light avoidance reduces ascorbic acid accumulation in the peel of Citrus fruit. (February 2015) - Lado, Joanna; Alós, Enriqueta; Rodrigo, María Jesús; Zacarías, Lorenzo
Highlights: Fruit bagging reduced AsA accumulation in the peel of citrus fruit. The l -galactose biosynthetic pathway was only marginally affected by light. Light avoidance markedly repressed specific isoforms from l -galacturonic pathway. l -galacturonic pathway contributes to the regulation of AsA pool. Abstract: Citrus fruits are highly consumed worldwide and represent one of the most important sources of ascorbic acid (AsA). However, information about the molecular mechanisms regulating AsA accumulation in Citrus fruit and the effects of environmental factors is scarce. In this study we have investigated the effect of fruit shading on AsA content and the expression of AsA biosynthetic, degrading and recycling genes in fruits of different Citrus species. Immature-green fruits were covered at the end of the cell enlargement phase and AsA concentration in the flavedo declined and remained at low levels as compared with light-exposed fruits. Fruit shading marginally altered the expression of genes from the l -galactose pathway and this effect was variable in the four Citrus species. However, specific isoforms ( GalUR8 or GalUR12 ) from the l -galacturonic acid pathway were significantly repressed paralleling the reduction in AsA concentration. No significant effect of shading was detected in transcription of genes of the myo -inositol and l -gulose pathways as well as recycling and degradation. Collectively, results indicate that light avoidance inhibited accumulation of AsA in the flavedo of Citrus fruits and suggest that the l -galacturonic acid pathway has a relevant contribution to AsA content in this tissue.